Penggunaan Jarak Tanam dan Pemangkasan yang Berbeda terhadap Pertumbuhan Vegetatif pada Kultivar Kedelai Hitam (Glycine Max L) - Ali Sanri; Rahmadina Rahmadina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the best treatment of spacing, pruning, and their interactions on vegetative growth in the black soybean cultivar Glycine max L. The method used was factorial RAK with 3 replications: 1st factor of Detam 3 (K1) and Detam 4 (K2) cultivars; 2nd factor, J1 = 20 cm 20 cm and J2 = 20 cm 40 cm; 3rd factor, -3 trimming (P1) and no trimming (P2). Parameters observed were plant height, number of active root nodules, number of leaves, number of production branches, and chlorophyll content. The results showed that the treatment of J1 spacing (20 cm x 20 cm) had a significant effect on all research parameters, namely plant height, number of production branches, number of leaves, chlorophyll content, and number of root nodules. Treatment P1 (pruning) had a significant effect on plant height and chlorophyll content; P2 (no pruning) had a significant effect on the number of production branches, number of leaves, and number of root nodules. Treatment of cultivar type K1 (Cultivar Detam 3) had a significant effect on all types of parameters. It can be concluded from this study that there is no interaction between planting distance, pruning, and cultivar type on vegetative growth in black soybeans (Glycine max L). Keywords: Plant spacing, Black Soybean, Cultivars, Pruning